Pengaruh Komitmen Kerja dan Kepuasan Kerja Terhadap Disiplin Kerja Karyawan Pada Kopi Janji Jiwa - Salma Shafa Salsabila (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of work commitment on the work discipline of the coffee promise of the soul, to determine the effect of job satisfaction on the work discipline of the coffee promise of the soul, and to know the effect of work commitment and job satisfaction on the discipline of the coffee promise of the soul. The sample used in this study were 37 coffee employees. This study used quantitative methods by collecting data through questionnaires and then testing the data using multiple linear regression analysis. The results of this study indicate (1) there is an effect of work commitment on the work discipline of coffee pledges of the soul. (2) There is an effect of job satisfaction on the work discipline of coffee pledges of the soul. (3) There is an effect of work commitment and job satisfaction on the work discipline of coffee-promise-spirit employees.